2019
DOI: 10.1097/md.0000000000016289
|View full text |Cite
|
Sign up to set email alerts
|

Improving the detection rate of prostate cancer in the gray zone of PI-RADS v2 and serum tPSA by using prostate-specific antigen–age volume

Abstract: To improve the detection of prostate cancer (PCa) by combining the Prostate Imaging Reporting and Data System version 2 (PI-RADS v2) and prostate-specific antigen–age volume (PSA–AV), especially among those in gray zone with PI-RADS v2 score 3 or serum total prostate-specific antigen (tPSA) 4 to 10 ng/mL. The 357 patients were enrolled in this study. The PI-RADS v2 scoring system was used to represent characteristics on multiparametric magnetic resonance imaging (mpMRI). PI-RADS v2 score 3 or tPSA 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…PI-RADS v2.0 using mpMRI, which has a superior image quality than TRUS, is used to diagnose prostate cancer. However, Lu et al [23] reported that MRI findings with a PI-RADS score of 3 or higher in patients with gray zone PSA level were at 38.2%, and the authors suggested using total PSA, PSAD, and PSA-age volume adjustments to improve the detection rate of prostate cancer in these patients.…”
Section: Logistic Regression Analysis According To Cut-off Values Of Various Parametersmentioning
confidence: 99%
“…PI-RADS v2.0 using mpMRI, which has a superior image quality than TRUS, is used to diagnose prostate cancer. However, Lu et al [23] reported that MRI findings with a PI-RADS score of 3 or higher in patients with gray zone PSA level were at 38.2%, and the authors suggested using total PSA, PSAD, and PSA-age volume adjustments to improve the detection rate of prostate cancer in these patients.…”
Section: Logistic Regression Analysis According To Cut-off Values Of Various Parametersmentioning
confidence: 99%
“…In terms of the pathological reference standard, all the studies employed TRUS-guided biopsy. Seven of these studies 20,23,28,29,31,34,36 also used cognitive MRI-TRUS fusion-guided biopsies. In addition, nine articles [24][25][26]28,29,31,32,34,36 used the PI-RADS score to interpret the images (PI-RADS v2, n = 8; PI-RADS v2.1, n = 1).…”
Section: Studies On Mri For Predicting Prostate Biopsy Resultsmentioning
confidence: 99%
“…Five studies 16,23,30,33,39 used 1 H MRS sequences in combination with other conventional sequences and 1 study 22 used only T2WI. With regard to MRI image interpretation, 12 studies 21,[24][25][26]28,29,31,32,34,[36][37][38] used the Prostate Imaging Reporting and Data System (PI-RADS) score. Out of these 12 studies, 10 used the PI-RADS v2 and 2 studies 31,37 used the PI-RADS v2.1.…”
Section: Mr Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…PI-RADS v2.0 using mpMRI, which has a superior image quality than TRUS, is used to diagnose prostate cancer. However, Lu et al [23] reported that MRI ndings with a PI-RADS score of 3 or higher in patients with gray zone PSA level were at 38.2%, and the authors suggested using total PSA, PSAD, and PSA-age volume adjustments to improve the detection rate of prostate cancer in these patients.…”
Section: Discussionmentioning
confidence: 99%